(untitled) (Conferencea, 2022)
The present paper aims at defining the notions of literary translation, its main peculiarities, and the notion of author’s style in literary interpretation. In addition, it investigates the problem of transferring writer’s individual style in translating literary texts. We focus on the importance of preserving author’s style, and on identifying the main principles of adequate transference of author’s style of writing.